Venoma comparativo de escolopendromorfos (Chilopoda, Scolpendromorpha) - Breno Rates Azevedo (2006)
Centipedes are venomous arthropods responsible for a significant but non-lethal number of human envenomations. Despite this, information about the composition and function of their venom contents is scarce. In this study we have used a bottom-up proteomic approach combining 2D-LC, ESI-Q-TOF/MS, N-terminal sequencing and similarity searching to better understand the complexities of the venoms from two Brazilian centipede species: Scolopendra viridicornis nigra and Scolopendra angulata. Comparisons between the LC profiles and the mass compositions of the venoms of the two species are provided. Also, the N-termini of representatives of 10 protein/peptide families were successfully sequenced where nine of them showed no significant similarity to other protein sequences deposited in the Swiss-Prot database. A screening for insetotoxic activity in fractions from S. viridicornis venom has also been performed. Six of the 12 tested fractions were responsible for clear toxic effects in house flies. This work demonstrates that centipede venoms might be a neglected but important source of new bioactive compounds.